PROTOTYPE OF HOUSE FIRE EARLY DETECTION SYSTEM USING FLAME SENSOR WITH TELEGRAM NOTIFICATION VIA THINGER.IO - Wahjudi, Dody; Sudaryanto, Eko; Ayu Margiyanti, Niken Dwi; Darmawan, Isra' Nuur (Program Studi Teknik Elektro Universitas Peradaban, 2024)
This research is based on the problem of gas leakage which is one of the factors causing fires to occur. Too slow a response of the homeowner to the occurrence of a fire disaster is a factor in fires that can cause loss of life and property that is not small. As an effort to prevent things that are not expected, a system that can detect fires effectively is needed. Designing a fire detection system that supports IoT (Internet Of Things) so that it can be monitored remotely is a suitable preventive alternative. Therefore, the design of a fire detection system using the NodeMCU ESP8266 microcontroller and input Flame sensor that can detect the presence of fire with a minimum detection distance of 10cm with an average voltage output of 5.076V while, the maximum detection distance is 100cm with an average voltage output of 5.066V. MQ-2 sensor to detect gas particles with an average output voltage of 4.99V. Dust sensors can detect paper smoke particles with an average voltage output of 5.066V at a smoke density of 848.90 while cigarette smoke with an average voltage output of 5.038 at a smoke density of 849.87. If one of the sensors detects a potential fire, it will automatically send a message to Telegram accompanied by a buzzer and LED that lights up as a warning sign. Thinger.io software to monitor data changes in the system.